2017
DOI: 10.1093/sleep/zsx126
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Wall Thickness in Obese and Nonobese Adults With Obstructive Sleep Apnea Before and Following Positive Airway Pressure Treatment

Abstract: Regardless of obesity status, carotid IMT is not increased in adults with moderate to severe OSA versus controls and does not change following 4 months of PAP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Previous research indicates that quantitative IMT and QAS techniques, as noninvasive examinations, provides a comprehensive evaluation of CCA remodeling for assessing preclinical atherosclerosis and early-stage diabetes (15,16,30). Although several studies have shown that there are no changes in carotid IMT in OSA patients compared to non-snorers (13,31), substantial evidence indicates a significant increase in OSA patients compared to non-snorers (32). In this study, we creatively used the ultrasound radiofrequency technology to detect changes in the structure and function of the carotid artery in OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that quantitative IMT and QAS techniques, as noninvasive examinations, provides a comprehensive evaluation of CCA remodeling for assessing preclinical atherosclerosis and early-stage diabetes (15,16,30). Although several studies have shown that there are no changes in carotid IMT in OSA patients compared to non-snorers (13,31), substantial evidence indicates a significant increase in OSA patients compared to non-snorers (32). In this study, we creatively used the ultrasound radiofrequency technology to detect changes in the structure and function of the carotid artery in OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The method of OSA diagnosis in PISA was described in detail previously. 16 Subjects were excluded with any unstable or new medical condition in the month prior to screening, severe and uncontrolled arterial hypertension (SBP >180 mmHg; DBP >110 mmHg), BMI >40 kg/m 2 , routine consumption of more than two alcoholic beverages per day, and excessive caffeine use (>10 cups/day). Pregnant women were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The method of OSA diagnosis in PISA was described in detail previously. 16 Subjects were excluded with any unstable or new medical condition in the month prior to screening, severe and uncontrolled arterial hypertension (SBP > 180 mm Hg; DBP > 110 mm Hg), BMI > 40 kg/ Subjects were included in the primary analyses if they underwent ABPM during screening for eligibility for PISA, whether or not they were found to have OSA, and if they were not on antihypertensive treatment for ≥2 months prior to screening.…”
Section: Pisa Study Designmentioning
confidence: 99%
“…Additionally, the same group demonstrated that effective treatment with CPAP therapy improves validated markers of atherosclerosis including arterial stiffness and CIMT [2]. However, a larger, more recent study examining the effects of OSA and CPAP on carotid atherosclerosis did not show an increase in CIMT in patients with OSA vs controls and did not show a change in CIMT after PAP therapy [35]. It is important to note that while there are several studies evaluating CIMT in OSA, carotid plaque burden or activity was not measured in these studies.…”
Section: Discussionmentioning
confidence: 99%